Cohort profile: study design and baseline characteristics of an observational longitudinal weight loss cohort and biorepository of patients undergoing sleeve gastrectomy in the USA - Melanie Jay; Eran Segal; Brian Elbel; Jose O Aleman; Sally M Vanegas; Silvia Curado; Akash Gujral; Gabriela Valverde; Susan Parraga; Migdalia Reid; Ann Marie Schmidt; Sean P Heffron; et al. (BMJ Open)
Purpose We developed a comprehensive sleeve gastrectomy (SG) weight loss study cohort and biorepository to uncover mechanisms, biomarkers and predictive factors of weight loss, weight maintenance and amelioration of obesity-related comorbidities. For this purpose, we collected psychosocial, anthropometric, clinical data and a variety of samples pre-surgery, intraoperatively and 1.5, 3, 12 and 24 months post-surgery. For longer-term assessment, the collection of psychosocial and anthropometric data was extended to 10 years. Here, we present in-depth characterisation of the cohort and detailed overview of study procedures as a foundation for future analyses.Participants We consented 647 participants between June 2017 and March 2020 from two bariatric surgery clinics in New York City—one major urban hospital and one private hospital. Of 355 participants who provided baseline data, 300 underwent SG. Of these, 79% are females with an average age of 38 years, 68% are Hispanic, 20% are non-Hispanic Black and 11% are non-Hispanic White.Findings to date We collected intraoperative adipose and stomach tissues from 282 patients and biosamples (blood, urine, saliva, stool) from 245 patients at 1.5 months, 238 at 3 month, 218 at 12 months and 180 at 24 months post-surgery. We are currently collecting anthropometric and psychosocial data annually until 10 years post-surgery. Data analysis is currently underway.Future plans Our future research will explore the variability in weight loss outcomes observed in our cohort, particularly among Black and Hispanic patients in comparison to their White counterparts. We will identify social determinants of health, metabolic factors and other variables that may predict weight loss success, weight maintenance and remission of obesity-related comorbidities. Additionally, we plan to leverage our biorepository for collaborative research studies. We will complete long-term follow-up data by December 2031. We plan to apply for funding to expand biosample collection through year 10 to provide insights into the mechanisms of long-term weight maintenance.